(untitled) (Педагогіка вищої та середньої школи, 2001)
In this article is considered the opportunities of chorus singing repertoire in developing moral-aesthetical values of pupils. The meaning of value is revealing. The philosophical and psychology-pedagogical literature about moral and aesthetical upbringing connection is analyzed about the emotional-moral influence of art on person. Modern methods to the tasks of music are considered as aesthetical upbringing of schoolchildren, caused by moral aesthetical nature of art-creativity.